2017
DOI: 10.1177/1757482x16688476
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of an annular water–air jet pump with self-induced oscillation mixing chamber

Abstract: This paper presents an improved annular water-air jet pump concept design through integrating a self-induced oscillation mixing chamber with the conventional annular jet pump (AJP). The internal flow characteristics for both conventional and improved AJP were numerically investigated and compared by a validated computational fluid dynamics model. The numerical comparison demonstrated an approximately 10% pumping performance increase compared with the conventional pump, which is mostly attributed to the improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…= P k t + Cd w Dw + @ @ x j ( + w t ) @! @ x j ; (15) where D w is the dissipation term and Cd w is the crossdi usion term for !, respectively. More speci cs are found in [28{30].…”
Section: The Numerical Model and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…= P k t + Cd w Dw + @ @ x j ( + w t ) @! @ x j ; (15) where D w is the dissipation term and Cd w is the crossdi usion term for !, respectively. More speci cs are found in [28{30].…”
Section: The Numerical Model and Methodologymentioning
confidence: 99%
“…Xiaogang et al [15] investigated numerically the ow characteristics for both traditional and ameliorated annular-water-air-jet-pump. Their study improved the annular-water-jet-pump performance by 10% compared with the traditional pump.…”
Section: Introductionmentioning
confidence: 99%
“…1, where water is used as the driving fluid and air is used as the entrained fluid. As mentioned earlier, the main difference between the conventional design and the improved design is the self-excited oscillation chamber, which is an enlarged cylindrical cavity with a cone-shaped impinge downstream sidewall, and its geometrical configuration was adopted from our previous work (Deng et al, 2017). The basic principle of the annular self-excited oscillating jet pump is that the pressurized working fluid forms a high-speed jet through the annular nozzle.…”
Section: Geometrical Parametersmentioning
confidence: 99%
“…The effect of the hydraulic characteristics of the jet pump is discussed, and the optimal mixing chamber structural parameters are derived. Deng et al (2017) investigated the modified jet pump by numerical simulation and found that self-introduced oscillations cause successive rupture and the formation of liquid-gas interfaces, and the phenomenon is characterized by periodicity. The results of this study help understand the flow pattern within the liquid-air jet pump and, thus, improve the unsteady operation of the pump.…”
Section: Introductionmentioning
confidence: 99%